Pengelompokan Jumlah Kecelakaan Lalu Lintas di Padang Menggunakan Analisis Cluster dengan Metode Non-Hirarki (K-Means) - Tiara Angela Hanami; Helma Helma (UNIVERSITAS NEGERI PADANG, 2023)
Traffic Accidents in August and July 2016. Traffic accidents in West Sumatra Province, especially in Padang City, are relatively high. Based on data from the Central Statistics Agency of Padang City, the number of traffic accident cases has increased from 2016-2021. This study aims to make a pattern in recognizing the characteristics of traffic accidents in the Padang City to minimize the increase in the frequency of accidents in the following year. This type of research is applied research. The result showed that optimizing clusters using the elbow method produced 4 clusters with categories: the first cluster included relatively high traffic accidents in 2021; the second cluster includes groups that have relatively moderate numbers in 2018 and cause material losses in 2021; the third cluster is relatively low, namely material losses in 2016 and 2018; the fourth cluster of very low traffic accidents in July and August 2016.